Antitumor and Immunomodulatory Activities of Ganoderma lucidum Polysaccharides in Glioma-Bearing Rats. (September 2018) - Wang, Chunhua; Shi, Songsheng; Chen, Quan; Lin, Shuqian; Wang, Rui; Wang, Saizhen; Chen, Chunmei
Malignant gliomas are the most common brain tumors with high rates of recurrence and mortality. Novel approaches are in research, and immunotherapy emerges as a promising strategy. Recently, scientific attention has been focused on Ganoderma lucidum polysaccharides (GL-PS), one of the critical bioactive components of G lucidum, which have been recognized as a promising natural source of immunomodulatory and anticancer compounds. It remains unknown whether the GL-PS have any immunomodulatory and anticancer effects on brain glioma. This study was designed to identify and characterize the antitumor action and influence of immune system of GL-PS in glioma-bearing rats. Results showed that GL-PS increased the concentration of serum interleukin-2, tumor necrosis factor-α, and interferon-γ, and enhanced the cytotoxic activity of natural killer cells and T cells, promoting the functional maturation of dendritic cells, thus resulting in the inhibition of glioma growth and prolonged survival of rats. Therefore, GL-PS may be potentially useful as part of the treatment regimen to regulate host immune responses and increase the antitumor effects of immunotherapy for glioma.